Letter from Julia Morgan to Cousin Lucy and Cousin Pierre Le Brun, July 19, 1897 - Julia Morgan::::::author::: (1897)
On July 19, 1897, Julia Morgan wrote to her cousins Lucy and Pierre Le Brun regarding her Ecole des Beaux Arts examinations. She recounts the difficulty of the examinations and her results. She tells of living with a girl from San Francisco and Paris beginning to feel like home. She tells of her travels with the Maybecks and Browns and her plans to board in Luzarches and study for the upcoming architectural examination.